2022
DOI: 10.1186/s12866-022-02528-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microRNAs and claudin-7 in Caco-2 cell line treated with Blastocystis sp., subtype 3 soluble total antigen

Abstract: Background Blastocystis sp., is a eukaryote of the large intestine, which is reported from almost all countries. The pathogenesis of this protist is not clear. The current study aimed to analyze the effects of Blastocystis sp., ST3 soluble total antigen (B3STA) on the microRNAs (miRNAs) involved in the gut permeability and also pro-inflammatory cytokines, occludin, and claudin-7. Methods Blastocystis sp., ST3 isolated from stool sample was purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…The expression level of mir-16 was evaluated using stem-loop reverse transcriptase and real-time PCR using primers and protocols, which were previously explained [ 19 ]. For this purpose, RNA was extracted using Trizol extraction protocol (BioMix) from serum samples, which were collected from enrolled participants.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression level of mir-16 was evaluated using stem-loop reverse transcriptase and real-time PCR using primers and protocols, which were previously explained [ 19 ]. For this purpose, RNA was extracted using Trizol extraction protocol (BioMix) from serum samples, which were collected from enrolled participants.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of extracted RNAs was determined by NanoDrop (NanoDrop Technologies, USA) apparatus, and RNA adjustment was performed before complementary DNA (cDNA) synthesis. cDNA was constructed for mir-16 and U6, as housekeeping gene, using cDNA synthesis kit (Pars Tous, Mashhad, Iran), as explained previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a most recently published study suggested that Blastocystis sp. ST3 can modulate the expression levels of microRNAs involved in the gut barrier integrity, and claudin-7 ( 54 ). Notably, claudin-7 is categorized among pre-sealing tight junction proteins and plays a critical role in reducing the permeability of the gut ( 55 ).…”
Section: The High Prevalence Of Blastocystis Sp In...mentioning
confidence: 99%